Pleiotropic effects of a recessive Col1a2 mutation occurring in a mouse model of severe osteogenesis imperfecta. - Michelangelo Corcelli; Rachel Sagar; Ellen Petzendorfer; Mohammad Mehedi Hasan; Fleur S van Dijk; Anna L David; Pascale V Guillot (PLoS ONE)
In Europe, approximately 85-90% of individuals with Osteogenesis Imperfecta (OI) have dominant pathogenic variants in the Col1a1 or Col1a2 genes whilst for Asian, especially Indian and Chinese cohorts, this ratio is much lower. This leads to decreased or abnormal Collagen type I production. Subsequently, bone formation is strongly reduced, causing bone fragility and liability to fractures throughout life. OI is clinically heterogeneous, with the severity ranging from mild to lethal depending on the gene and the type and location of the OI-causative variant and the subsequent effect on (pro) collagen type I synthesis. However, the specific effects on the phenotype and function of osteoblasts are not fully understood. To investigate this, one of the OI murine models was used, i.e. the oim/oim (OIM) mice, which closest resembling severely deforming OI in humans. We showed that in OIM, the Col1a2 mutation results in a multifactorial inhibition of the osteogenic differentiation and maturation as well as inhibition of osteoclastogenesis. The phenotype of differentiated OIM osteoblasts also differs from that of wild type mature osteoblasts, with upregulated oxidative cell stress and autophagy pathways. The extracellular accumulation of defective type I collagen fibres contributes to activation of the TGF-β signalling pathway and activates the inflammatory pathway. These effects combine to destabilise the balance of bone turnover, increasing bone fragility. Together, these findings identify the complex mechanisms underlying OI bone fragility in the OIM model of severe OI and can potentially enable identification of clinically relevant endpoints to assess the efficacy of innovative pro-osteogenic treatment for patients with OI.